Pengaruh Profit Margin (Net Income to Net Sales Ratio), Total Assets Turn Over (Net Sales to Total Assets) dan Leverage (Total Assets to Equity) terhadap Return On Equity pada PT. Virama Karya Jakarta (Persero) - Ferriswara, Dian (Sekolah Tinggi Ilmu Ekonomi H. Agus Salim Bukittinggi, 2010)
Financial Management Analysis; The influencer of: Profit Margin (Net Income to Net Sales Ratio), Total Assets Turn Over (Net Sales to Total Assets) and Leverage (Total Assets to Equity) to Return On Equity, Case Study at Persero PT. Virama karya Jakarta (Government Company). An external condition, which are; limited market volume being caused by late approval of DIP (Daftar Isian Proyek) by goevernment and distric autonomy system that limiting access and rising competition, and globaly free market. Company has to strive to work effectively, efficient and have a good financial system policy. The main purpose of this research to analyze financial ratio of government company: Persero PT. Virama Karya Jakarta (management consultant caompany in civil engineering). Problem identification are: 1. Financial Ratio Policy; 2. How far influencer of Profit Margin Ratio (Net Income to Net Sales Ratio), Total Assets Turn Over (Net Sales to Total Assets) and Leverage (Total Assets to Equity) to Return On Equity, simultaneously or partially; 3. Influence of Debt to Profit Margin; 4. Influencer of Cahs Ratio to Company Value; 5. Influence of Return On Investment to Return On Equity; 6. Receivable Activity Turn Over to Cash Flow that influence profitability; 7. Return on Assets, Debt to Equity, Bank Rate Ratio and Tax simultaneously influence to equity growth in a Persero consultant company. The hypothesis is; there is an influence of Profit Margin Ratio (Net Income to Net Sales Ratio), Total Assets Turn Over (Net Sales to Total Assets) and Leverage (Total Assets to Equity) to Return on Equity, simultaneously or partially. We use case study method, which is descriptive analysis. Data collecting technique being used are report study, obervation and direct correspondence interview with Kepala Biro Keuangan Mr. Rully Soeparto.